O banho de rio: um mergulho na tradição amazônica. - Ricardo José Batista Nogueira (Confins)
This text proposes a reflection on the formation of river bath places as an area intended for social leisure and also as alternative spaces the sea. First, it presents a fundamental distinction between seawater and freshwater, the fundamental characteristics of each, and describes how social practices and culture have developed habits of structuration and social use. It recovers the tradition of river bathing while showing this habit, long-rooted in the habit of the local population, has been abandoned for various reasons. It shows the use of the rivers and streams of the Amazon as recreational areas of traditional uses. Finally, it shows the structural forms of the bathing areas of the city of Manaus.